2017
DOI: 10.1177/1098611117697056
|View full text |Cite
|
Sign up to set email alerts
|

The Current and Potential Role of Crime Analysts in Evaluations of Police Interventions: Results From a Survey of the International Association of Crime Analysts

Abstract: Crime analysts play a pivotal role in evidence-based policing by readily diagnosing the nature of crime and disorder problems. Such analysis products are key in the design of evidence-based strategies. The role of analysts in the subsequent process of evidence-based policing, the evaluation of programs to determine what works, is less known. The current study seeks to fill this gap in the literature through a survey of the International Association of Crime Analyst Membership. Findings suggest that program eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
1
10
1
2
Order By: Relevance
“…While crime analysts fulfilled this role in our risk-based policing projects, they were also oftentimes drivers of the project within their agencies. This suggests that crime analysts can potentially play a larger role in evidence-based policing than has traditionally been envisioned (Lum and Koper 2017;Piza and Feng 2017). Unfortunately, the role of crime analysts can be hindered by a police culture and organizational hierarchy that takes little notice of civilian staff (Santos and Taylor 2014;Taylor et al 2007), given that crime analysts are primarily staffed by non-sworn personnel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While crime analysts fulfilled this role in our risk-based policing projects, they were also oftentimes drivers of the project within their agencies. This suggests that crime analysts can potentially play a larger role in evidence-based policing than has traditionally been envisioned (Lum and Koper 2017;Piza and Feng 2017). Unfortunately, the role of crime analysts can be hindered by a police culture and organizational hierarchy that takes little notice of civilian staff (Santos and Taylor 2014;Taylor et al 2007), given that crime analysts are primarily staffed by non-sworn personnel.…”
Section: Resultsmentioning
confidence: 99%
“…However, had we planned for it at the outset of the project, crime analysts could have played a more direct role in these portions of the project. Piza and Feng (2017) recommend that researcher/practitioner partnerships embrace the knowledge-exchange feature of action research, which would directly expose crime analysts to the procedural aspects of rigorous research and evaluation. Ideally, this could lead to crime analysts Bdeveloping skills they can employ in their day-to-day duties^and allow them to Bdisseminate these newfound skills within her or his agency^ (Piza and Feng 2017, p. 360).…”
Section: Pd-bmentioning
confidence: 99%
“…Researcher-practitioner partnerships have often been advanced as a vehicle for better integrating EBP into police functions. Practitioners benefit from the analytical expertise of their research partners in exchange for the data access necessary to explore real-world problems, which can elude researchers outside of such partnerships (Piza & Feng, 2017). The analytical benefits to researchers vary in scope and have the potential to inform performance monitoring activities.…”
Section: Evidence-based Policing (Ebp) and The Role Of Researcher-practitioner Partnershipsmentioning
confidence: 99%
“…Research has also indicated that crime analysts may see themselves as serving a variety of functions within police departments (Piza and Feng, 2017). Most frequently, analysts view themselves as assisting in investigations, creating reports, and managing data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, analysts also saw themselves as examining trends and patterns, as well as generating and providing crime statistics, or engaging in weekly reporting. Although certainly appearing less often, Piza and Feng (2017) also noted that there may be expectations for analysts to engage in program evaluation for the department in which they are employed. Clearly, variation exists in the breadth of duties placed on analysts both within and between police organizations.…”
Section: Literature Reviewmentioning
confidence: 99%